Historia autyzmu: od baśni i legend po badania genetyczne – laboratorium budowy mitów w nauce - Osóbka, Krzysztof (Studia Edukacyjne, 2020)
Osóbka Krzysztof, Historia autyzmu: od baśni i legend po badania genetyczne – laboratorium budowy mitów w nauce [History of Autism: from Fairy Tales and Legends Through Genetic Research – a Laboratory of Building Scientific Myths]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 339-367. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.19 Autism is one of the most mysterious human disorders ever known. Although existent from the dawn of humanity, it was only in 1943 that science took up this subject. Before, undiscovered and unnamed, it was considered merely a legend, and the only existing records were those of few pioneer case studies. The discoveries of Leo Kanner, the first person to properly define autism, marked the onset of a struggle to describe the disorder using scientific jargon. Unfortunately, the trials were not always successful. Autism, as described by contemporary science, is a neurodevelopmental disorder. Theories claiming its psychogenic etiology can no longer be sustained. The history of research concerning autism points to a phenomenon known as collective thinking, a term coined by Ludwik Fleck, as well as to the process of the emergence of a scientific myth. It is a study of how researchers’ presuppositions can shape social beliefs and at the same time how constructing scientific theories is inherently ingrained in the cognitive style of an era. The second half of the 20th century marks the beginning of a gradual change in the classification of autism. The perception of the nature of this disorder shifted from psychogenic theories to organic etiologies. It was the voice of the enormously talented and creative individuals with high-functioning autism, a voice rejected until the 1980s, that triggered a breakthrough in relevant research.